2016
DOI: 10.1051/matecconf/20178702013
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Relationship Between Carrying Schoolbags and The Prevalence of Neck and Back Pain Among 7 – 9 Year Old Students

Abstract: Abstract. There is a growing concern these days that children are carrying way too much weight on their backs. School students are at risk of developing Musculoskeletal Disorder or possibly long term back pain due to the frequent exposure of carrying heavy schoolbags. In Malaysia, this problem is currently an overlooked issue as not many are aware of the importance of maximum allowable load that should be carried by school students together with proper posture and how all these will affect the children in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…[ 15 ] Another research study showed that school bag design also plays important role in prevalence of neck and back pain. [ 16 ] The study also shows other important predictor, i.e., leaning forward when carrying school bag where musculoskeletal pain was increased by 1.73 times who lean forward while carrying their bags and results in negative change in the posture. Another research study also reported that increase in the weight of school bag may lead to spine pain as well as negative change in body posture.…”
Section: Discussionmentioning
confidence: 69%
“…[ 15 ] Another research study showed that school bag design also plays important role in prevalence of neck and back pain. [ 16 ] The study also shows other important predictor, i.e., leaning forward when carrying school bag where musculoskeletal pain was increased by 1.73 times who lean forward while carrying their bags and results in negative change in the posture. Another research study also reported that increase in the weight of school bag may lead to spine pain as well as negative change in body posture.…”
Section: Discussionmentioning
confidence: 69%
“…They concluded that heavy school bags can cause physical pain such as back pain, shoulders and neck pain if not be carried properly. Further, (Kabilmiharbi & Santhirasegaram, 2016) conduct a study in Malaysia to find out the association of heavy school bags and occurrence of neck and back pain in children of primary school in Shah Alam, Selangor and result exposed that due to heavy school bags, improper mode and time duration of carrying bags occurrence of neck and pain were happen nearly in 90 students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assimilation of information arising from proprioceptive, vestibular and visual systems is also necessary for body balance [10]. School understudies are mindful on conveying their own schoolbag thus it is imperative for every understudy to convey their schoolbag legitimately with a specific end goal to evade or limit postural issues, back agony and musculoskeletal issue [11]. Heavy backpacks carried on regular basis can change the curvature of the spine.…”
Section: Introductionmentioning
confidence: 99%